Strategi Peningkatan Kawasan Wisata Kuliner Pantai Tak Berombak di Kecamatan Turikale, Kabupaten Maros - Kezia Christin Sesa; Murshal Manaf; Emil Salim; Jamilah Abbas (Fakultas Teknik Universitas Bosowa, 2023)
The purpose of this study is to find out what factors are the main attraction of the Culinary Tourism Area on the Unwaved Beach and to find out the strategy for improving the Culinary Tourism Area on the Unwaved Beach in Turikale District, Maros Regency. The approach of this research is to use qualitative and quantitative approaches which then use chi-square analysis to determine the factors that are the main attraction of the Culinary Tourism Area of ​​the Unwaved Beach and use SWOT analysis to determine strategies for improving the Culinary Tourism Area of ​​the Unwaved Beach. The conclusion of this study is that there are three factors that are the main attraction of the Tak Wavy Beach Culinary Tourism Area, namely tourism activities (availability of culinary delights), accessibility (condition of the road network and easy access) and public facilities (security posts, parking lots, mosques). The strategy that can be used in improving the Unwaved Beach Culinary Tourism Area is the ST (strength-threat) strategy which uses all strengths to minimize threats.